2008
DOI: 10.4037/ajcc2008.17.4.357
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Tube Thoracostomies Performed by Advanced Practice Providers vs Trauma Surgeons

Abstract: Background The role of advanced registered nurse practitioners and physician assistants in emergency departments, trauma centers, and critical care is becoming more widely accepted. These personnel, collectively known as advanced practice providers, expand physicians’ capabilities and are being increasingly recruited to provide care and perform invasive procedures that were previously performed exclusively by physicians. Objectives To determine whether the quality of tube thoracostomies performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 34 publications
0
7
0
2
Order By: Relevance
“…Four studies compared PAs' skills in performing procedures. These are presented in Table 3 41–44 . PAs appear equally capable of performing procedures if adequately trained and supervised.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies compared PAs' skills in performing procedures. These are presented in Table 3 41–44 . PAs appear equally capable of performing procedures if adequately trained and supervised.…”
Section: Resultsmentioning
confidence: 99%
“…In a national survey of pediatric surgeons, nearly all respondents endorsed that integration of APPs in inpatient and outpatient settings positively impacted care, particularly with regard to continuity of care, efficiency of service, education of parents and patients, and patient satisfaction. 19 Single-center studies have shown that APPs can safely perform a range of procedures that were previously performed exclusively by physicians, such as thoracostomy insertion, 3 upper endoscopy, 4 and newborn circumcision. 5 In the immediate postoperative period, increased presence of APPs may help with early recognition of patients at risk of clinical deterioration and promote timely escalation of care.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies on the subject have focused thus far on relatively minor procedures performed within single centers. [3][4][5][6] Evidence from nonsurgical settings suggests that APPs may facilitate the delivery of care through enhanced care coordination and communication and by providing coverage in light of resident duty hour restrictions. 7 Task sharing may allow physicians to focus on patients with complex needs where advanced training may have a larger marginal impact on health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…El diagnóstico y tratamiento de los traumatismos torácicos dependen en su mayor parte de la magnitud de la lesión y de la evidencia de lesiones asociadas. En la mayoría de los pacientes con lesiones por traumatismo de tórax resulta factible su resolución en forma conservadora, son manejados con buenos resultados mediante el drenaje de cavidad pleural con sondas o tubos pleurales 3,6,7 .…”
Section: Introductionunclassified
“…Las caídas y los accidentes vehiculares son las causas más comunes de traumatismo torácico en la literatura internacional [6][7][8]10 . En nuestro medio aparecen como una de las causas mas frecuentes, aunadas a las lesiones producidas por arma blanca, producto de riñas y asaltos.…”
Section: Introductionunclassified